Relationship of the Cycle in Yields of Cotton and Apples to Solar and Sky Radiation - Fulmer, J. L. (Quarterly Journal of Economics, 1942)
Introduction: the problem studied, 385. — The cycle in yields of certain crops, 388. — Sunspots and the solar constant and the cycle in yield of cotton, 392. — Solar and sky radiation and the cycle in yields of cotton and apples, 396. — Reasons for the correlation observed, 398. — Misconceptions in earlier investigations, 403. — Summary and conclusions, 403.